Sir Douglas Mawson the story of the Australasian Antarctic Expedition (1911-1914) - University of Adelaide (Adelaide, S.A. : University of Adelaide, 1996)
"An interactive insight into his leadership and the heroic events of the Australasian Antarctic Expedition of 1911-1914, which eventually led to the great explorer's knighthood"
Produced by the University of Adelaide and Bridgehead Australia Pty Ltd.
"This CD-ROM has been produced using artifacts, images, papers and books from the Mawson Antarctic Collection ... stored in the Coach House, part of the Urrbrae House Historic Precinct; on the Waite Waite Campus of the University of Adelaide."
System requirements: Windows 3.1. & 95 Hardware: MPC Level II multimedia computer with 486SX processor or higher. 8 Mb RAM (16 Mb recommended), double speed CD-ROM drive or faster. 8 bit sound card, speakers and maximum 245 colour screen display. Macintosh hardware: Mac LC630 or faster, 8 Mb RAM (16 Mb recommended). System 7 or higher, double speed CD-ROM drive.
Keywords: Mawson, Douglas, -- Sir, -- 1882-1958.; Antarctica -- Discovery and exploration -- Australian -- Software; CD-ROMs.; Interactive multimedia